A mechanistic study on the SHi reaction at tin atoms in a radical cascade reaction1. Issue 6 (15th June 2015) - Kamimura, Akio; Yoshinaga, Tatsuro; Noguchi, Fumiaki; Miyazaki, Koichiro; Uno, Hidemitsu
<x xml:space="preserve">Abstract</x> A kinetic study on the intramolecular direct radical substitution reaction on tin atoms was undertaken.